Pengembangan Media Pembelajaran Interactive Android Game Petualangan Syariahku pada Mata Pelajaran Layanan Lembaga Keuangan Syariah - Nattaya Lakshita Melati; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
As technology develops rapidly, adjustments the learning process are needed to achieve learning objectives. Curriculum 2013 with a scientific approach and technology ICT as an interactive learning tool is one of the methods to increase student interest and learning outcomes. Interactive Android game has a positive impact on motivation, enjoyment of learning, and confidence in the new information obtained. Equipped with various HOTS-based questions, appropriate designs, effective and efficient Android-based. This research aims to create interactive Android games for Islamic financial institution services class XI semester 1. The development process includes the analysis, design, development, implementation, and evaluation according to the ADDIE model by Dick and Carry. The media that has been developed is analyzed and tested on 20 students of Islamic banking class XI State Vocational High School 2 Mojokerto City. Average percentage results by experts and learners were obtained in the categories of